Ocular vestibular evoked myogenic potential in patients with benign paroxysmal positional vertigo - Mozhgan Masoom (Audiology, 2014)
Background and Aim: Since utricle is the main damaged organ in benign paroxysmal positional vertigo (BPPV), ocular vestibular evoked myogenic potential (oVEMP) may be an appropriate method to evaluate the utricule dysfunction and the effect of disease recurrence rate on it. This study aimed to record myogenic potential in patients with benign paroxysmal positional vertigo.Methods: In a cross-sectional study, ocular myogenic potential was recorded in 25 healthy subjects and 20 patients with benign paroxysmal positional vertigo using 500 Hz-tone bursts (95 dB nHL).Results: In the affected ear, mean amplitude was lower and mean threshold was higher than those in the unaffected ear and in the normal group (p<0.05). Mean amplitude asymmetry ratio of patients was more than the healthy subjects (p0.05). Frequencies of abnormal responses in the affected ears were higher than in unaffected ears and in the normal group (p<0.05). Furthermore, the patients with recurrent vertigo showed more abnormalities than the patients with non-recurrent (p=0.030).Conclusion: In the recurrent benign paroxysmal positional vertigo, ocular vestibular evoked myogenic potential showed more damage in the utricle, suggesting this response could be used to evaluate the patients with benign paroxysmal positional vertigo.